Effect of Relative Humidity on Survival of Candida albicans and Other Yeasts - Mackenzie, D. W. (1971)
Individual blastospores of Candida albicans were deposited on the surface of 50-mm membranes (Millipore Corp.) and placed within sealed glass chambers at various relative humidities (RH). After 48 hr, virtually all cells maintained at 100 and 10% RH had survived, but 84% of the cells maintained at 60% RH failed to develop into colonies when transferred to Sabouraud medium. No morphological abnormalities could be observed in cells surviving low RH values, but their initial rate of multiplication after transfer to Sabouraud medium was greatly reduced, compared to that demonstrated by cells maintained at 100% RH. At 60% RH, the exposure time required to kill 50% of the blastospores was 2 to 3.5 days. The inimical effect of 60% RH was confirmed in a total of 21 isolates of C. albicans. No deleterious effect was noted when 12 other species of yeasts were subjected to 10, 60, and 100% RH. The single isolate of Candida brumptii and 1 out of the 20 isolates of Cryptococcus neoformans tested also failed to grow after blastospores had been exposed to 60% RH for 4 days.